An Analysis of The Ability of Writing Narrative Text of The Tenth Grade Students of SMA Dharma Ayu Kefamenanu - Merlin Helentina Napitupulu; Yosefa Yemayo Ngao; Anselmus Sahan (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This study focuses on examining the writing skills of tenth-grade learners at SMA Dharma Ayu Kefamenanu in crafting narrative texts during the academic year 2023/2024. Utilizing a descriptive qualitative approach, the research involved a sample of 30 students chosen through purposive sampling methods. Data were gathered from students' written narrative texts, which were subsequently assessed based on five key components of writing: content, organization, vocabulary, language usage, and mechanics. The results indicated that the students’ overall writing proficiency was categorized as "fair," with content and organization receiving relatively higher ratings, while language usage and mechanics were pinpointed as areas requiring enhancement. The majority of students managed to create a fundamental narrative structure, comprising orientation, complication, and resolution, yet faced challenges with grammar precision, suitable vocabulary, and punctuation. The results suggest that although students show comprehension of narrative elements, their technical writing abilities are somewhat inadequate. In light of these outcomes, it is recommended that English instructors offer more targeted teaching and constructive feedback on grammar and writing conventions to improve students’ writing skills overall. This research sheds light on the existing proficiency in narrative writing among high school students and provides valuable insights for curriculum improvement and teaching methods aimed at boosting English writing capabilities.